2005
DOI: 10.1007/s00259-005-1762-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain glucose metabolism in the early and specific diagnosis of Alzheimer?s disease

Abstract: The demographics of aging suggest a great need for the early diagnosis of dementia and the development of preventive strategies. Neuropathology and structural MRI studies have pointed to the medial temporal lobe (MTL) as the brain region earliest affected in Alzheimer's disease (AD). MRI findings provide strong evidence that in mild cognitive impairments (MCI), AD-related volume losses can be reproducibly detected in the hippocampus, the entorhinal cortex (EC) and, to a lesser extent, the parahippocampal gyrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
585
3
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 763 publications
(629 citation statements)
references
References 180 publications
28
585
3
13
Order By: Relevance
“…Curiously, our subjects generally reported that the route perspective was more difficult to learn then the survey perspective (unquantified). Right frontal (~BA 4, 6) and left parietal (~BA 37,39,40) areas also appeared more active during route than survey encoding in APOE*4− subjects. Failure of prefrontal activation to increase with increasing task demands has been observed in APOE*4+ subjects (44) and thus the lack of a prefrontal route/survey differential may illustrate impaired prefrontal recruitment during difficult tasks in APOE*4− subjects.…”
Section: Perspective Dependent Mtl Activationmentioning
confidence: 91%
See 1 more Smart Citation
“…Curiously, our subjects generally reported that the route perspective was more difficult to learn then the survey perspective (unquantified). Right frontal (~BA 4, 6) and left parietal (~BA 37,39,40) areas also appeared more active during route than survey encoding in APOE*4− subjects. Failure of prefrontal activation to increase with increasing task demands has been observed in APOE*4+ subjects (44) and thus the lack of a prefrontal route/survey differential may illustrate impaired prefrontal recruitment during difficult tasks in APOE*4− subjects.…”
Section: Perspective Dependent Mtl Activationmentioning
confidence: 91%
“…Imaging with PET and SPECT lend support to the hypothesis that the APOE*4 allele worsens AD, with both increased (29,39) and decreased (17,35,39,51) resting metabolism being reported in demented APOE*4 carriers as compared to demented non-carriers. In MCI, carriers of the APOE*4 allele reduced metabolism in the parietal-temporal regions and medial parietal lobe, including the posterior cingulate and retrosplenial area (40), perhaps reflecting greater pathologic burden and worse prognosis for these patients (for review see (10,41)). PET and SPECT metabolic studies also reveal hypometabolism in younger (47,53) and older (48,52,59) cognitively unimpaired APOE*4+ subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is increasingly viewed as a disorder of brain metabolism, an invariant feature of which is a profound reduction in cerebral glucose metabolism 1, 2, 3. The impairment in glucose uptake and metabolism starts decades before classic AD symptoms and worsens steadily with disease progression 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, cognitive, motor, and behavior abnormalities underlie a variety of neurological dysfunctions associated with neurodegenerative disorders and HIV-1 infection. Thus, combinations of clinical, laboratory, and neuroimaging tests, while not irrefutably conclusive, are essential to provide diagnostic support [63][64][65][66]. A wide range of neuroimaging techniques can aid in the diagnosis of neurological complications associated with neurodegenerative disorders.…”
Section: Bioimaging Of the Cnsmentioning
confidence: 99%